2007
DOI: 10.3844/jcssp.2007.723.725
|View full text |Cite
|
Sign up to set email alerts
|

Feature Selection in Data-Mining for Genetics Using Genetic Algorithm

Abstract: Abstract:We discovered genetic features and environmental factors which were involved in multifactorial diseases. To exploit the massive data obtained from the experiments conducted at the General Hospital, Chennai, data mining tools were required and we proposed a 2-Phase approach using a specific genetic algorithm. This heuristic approach had been chosen as the number of features to consider was large (upto 3654 for biological data under our study). Collected data indicated for pairs of affected individuals … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…This shows that the k-means algorithm using results of the GA, is able to construct clusters very closely related to the solution pre-sented in results of the workshop. Moreover this solution has been exactly found 4 times over 10 of executions [3].The genetic algorithm managed to select interesting features and the k-means algorithm was able to class pairs of individuals according to these features and to confirm interesting associations of features [3].  Chan Wai Keung Brian (2006): The advantage of using genetic algorithm [4] is that it does not have to know any rules of the prob-lem in advancethe rule will can be found through evolution.…”
Section: Literature Studymentioning
confidence: 85%
“…This shows that the k-means algorithm using results of the GA, is able to construct clusters very closely related to the solution pre-sented in results of the workshop. Moreover this solution has been exactly found 4 times over 10 of executions [3].The genetic algorithm managed to select interesting features and the k-means algorithm was able to class pairs of individuals according to these features and to confirm interesting associations of features [3].  Chan Wai Keung Brian (2006): The advantage of using genetic algorithm [4] is that it does not have to know any rules of the prob-lem in advancethe rule will can be found through evolution.…”
Section: Literature Studymentioning
confidence: 85%
“…This shows that the k-means algorithm using results of the GA, is able to construct clusters very closely related to the solution presented in results of the workshop. Moreover this solution has been exactly found 4 times over 10 of executions [3].…”
mentioning
confidence: 80%
“…The genetic algorithm managed to select interesting features and the k-means algorithm was able to class pairs of individuals according to these features and to confirm interesting associations of features [3].…”
mentioning
confidence: 99%
“…Several researchers ( Vafaie and Jong, 1992;Kohavi and John, 1997;Yang and Honavar, 1998;Pernkopf and O'Leary, 2001;Fröhlich and Chapelle, 2003;Yu and Cho, 2006;Huang and Wang, 2006;Faraoun and Rabhi, 2007;Rajavarman et al, 2007;Ramirez and Puiggros, 2007;Xia et al, 2009) have employed the genetic algorithm as a search tool in feature subset selection in their work. All these investigations have confirmed that the GA-generated feature subsets perform better than the initial universal set or the full feature set.…”
Section: Related Workmentioning
confidence: 99%